The effect of group counseling based of problem solving techniques to reduce of online game addiction among students - Hosin Hosin (Indonesian Institute for Counseling, Education and Theraphy, 2021)
This study intends to investigate the influence of group counseling with problem-solving approaches on class VI students of MI Al-Istiqamah Banjarmasin who are addicted to playing online games.This investigation employs pure experimental research (True-Experimental design) in conjunction with the Pretest Posttest Control Group Design model. Purposeful sampling was used to identify research volunteers. 16 sampled, with eight from the experimental group and eight from the control group.Applying the Cronbach alpha formula and the SPSS for Windows version 23.0 application, examine the instrument's validity using the questionnaire.The prerequisite examination for analysis consists of a normalcy test and a hypothesis test.The analysis of data employed non-parametric statistical methods, namely the Mann-Whiteney test using SPSS for Windows version 23.0.The results demonstrated that group counseling with problem-solving strategies reduced the prevalence of online game addiction. This is supported by the Mann-Whiteney test results for the experimental group, which yielded a probability value of sig (2-tailed) 0.022 0.05. Based on the analysis and discussion, there is a difference between the experimental and control groups' average scores on the online gaming addiction questionnaire before and after receiving therapy. Group counseling using problem-solving approaches has an effect on reducing the amount of online game addiction, according to the study's findings.